Altered Gut Microbiota Associated With Hemorrhage in Chronic Radiation Proctitis - Liu, Liangzhe; Chen, Chaoyun; Liu, Xia; Chen, Bingcheng; Ding, Chen; Liang, Jinjun (Frontiers in Oncology, 2021)
Pelvic cancer radiotherapy may cause chronic radiation proctitis (CRP) that adversely affects patient’s quality of life, especially in patients with prolonged hematochezia. However, previous studies of radiation enteropathy mainly focused on acute irradiation hazards, and the detailed pathogenesis process and mechanism of prolonged hematochezia associated with radiation-induced toxicity remain unclear. In this study, we characterized the gut microbiota of 32 female CRP patients with or without hematochezia. Differential patterns of dysbiosis were observed. The abundance of Peptostreptococcaceae, Eubacterium, and Allisonella was significantly higher in CRP patients with hematochezia, while the compositions of the Lachnospiraceae, Megasphera, Megamonas, and Ruminococcaceae were lower in the microbiota of non-hematochezia patients. Functional prediction suggested significant difference in the expression of mineral absorption and the arachidonic acid metabolism proteins between hematochezia and non-hematochezia patients, possibly interdependent on radiation-induced inflammation. This study provides new insight into the altered composition and function of gut microbiota in patients with hematochezia, implying the potential use of probiotics and prebiotics for assessment and treatment of CRP.